Gut microbiome metabolites as key actors in atherosclerosis co-depression disease - Liao, Xing-Xing; Wu, Xiao-Yun; Zhou, Yu-Long; Li, Jia-Jun; Wen, You-Liang; Zhou, Jun-Jie (Frontiers in Microbiology, 2022)
Cardiovascular diseases, mainly characterized by atherosclerosis (AS), and depression have a high comorbidity rate. However, previous studies have been conducted under a single disease, and there is a lack of studies in comorbid states to explore the commonalities in the pathogenesis of both diseases. Modern high-throughput technologies have made it clear that the gut microbiome can affect the development of the host's own disorders and have shown that their metabolites are crucial to the pathophysiology of AS and depression. The aim of this review is to summarize the current important findings on the role of gut microbiome metabolites such as pathogen-associated molecular patterns, bile acids, tryptophan metabolites, short-chain fatty acids, and trimethylamine N -oxide in depression and AS disease, with the aim of identifying potential biological targets for the early diagnosis and treatment of AS co-depression disorders.